Development Strategy of Babana Mangrove Ecotourism in Larompong Selatan District, Luwu Regency - Wahyuti, Wahyuti; Ummung, Andi; Massiseng, Andi Nur Apung; Daris, Lukman; Nurwahidah (Hasanuddin University, 2023)
The mangrove ecosystem in the Babana area has the potential for developing ecotourism activities. This study aims to identify the potential of the Babana mangrove ecotourism in Larompong Selatan District, and to analyze the Babana mangrove ecotourism development strategy in Larompong Selatan District. This research was conducted from May to July 2022 and was carried out in the Babana mangrove ecotourism area, Larompong Selatan District, Luwu Regency, South Sulawesi Province. Data collection was carried out through field surveys and interviews using a questionnaire. The method used in this study was SWOT analysis. The results of this study indicate that the potential for Babana mangrove ecotourism is the uniqueness of the mangrove ecosystem lies in the presence of a rainbow bridge which is the main attraction for Babana mangrove ecotourism. The Babana mangrove ecotourism development strategy has great opportunities but also has weaknesses. The strategy for developing the Babana mangrove ecotourism in Larompong Selatan District, Luwu Regency, is to create complex concepts related to the development of mangrove ecotourism by the interests of visitors and involve the community to participate in it, improve facilities and infrastructure and increase human resources for the development of mangrove ecotourism, increase the attractiveness and cleanliness and safety of ecotourism mangroves, and optimizing promotion and interpretation for visitors.